Perancangan Interior Pusat Informasi Peralatan Fisika di Surabaya - Andereas Pandu Setiawan, Garry Nathaniel Abet (Intra, 2014)
This design is aimed to educate the Surabayaâs people about equipment and physics knowledge. Remembering the general peopleâs circumscription about physics education. The design that I create is designing information centre as functional as possible. Physics equipment can help Surabayaâs people to increase their knowledge about physics education.